2020
DOI: 10.1109/access.2020.2965979
|View full text |Cite
|
Sign up to set email alerts
|

Industry 4.0 Development Multi-Criteria Assessment: An Integrated Fuzzy DEMATEL, ANP and VIKOR Methodology

Abstract: Industry 4.0 (I4.0) includes an important regeneration of production and management systems within manufacturing, where the majority of the procedures will be entirely or partially automated. However, there are insufficient research studies related to I4.0 development assessment based on the various requirement factors to enable countries to measure their own conditions and to make future national strategies and roadmaps for their activities in this field. Thus, this paper develops a comprehensive framework to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The Step Wise Weight Assessment Ratio Analysis (SWARA) method was one of the newest methods used in 2010 by Cresolin et al regarding the selection of a reasonable difference analysis method. This method is similar to the AHP [34] and ANP [35] methods, which are used to calculate the criteria weights in multicriteria decision-making problems. In this method, the experts first prioritize the criteria, and the most important criterion then takes the highest (top) priority.…”
Section: The Swara Methodsmentioning
confidence: 99%
“…The Step Wise Weight Assessment Ratio Analysis (SWARA) method was one of the newest methods used in 2010 by Cresolin et al regarding the selection of a reasonable difference analysis method. This method is similar to the AHP [34] and ANP [35] methods, which are used to calculate the criteria weights in multicriteria decision-making problems. In this method, the experts first prioritize the criteria, and the most important criterion then takes the highest (top) priority.…”
Section: The Swara Methodsmentioning
confidence: 99%
“…In these studies, the criteria were selected first and the most important issues were calculated with the DEMATEL method [56,57]. In addition to the issues mentioned, some researchers also preferred this method to define the factors that influence service innovation [58,59]. Moreover, the DEMATEL method has been used in some studies to increase the efficiency of energy production [60,61].…”
Section: Literature On Methodologymentioning
confidence: 99%
“…In this context, the average (D − E) value is firstly calculated, and it is compared with the values in the total relation matrix. For the values that are greater than the average value, it is identified that the first criterion influences another one [59].…”
Section: B = B Ij N×nmentioning
confidence: 99%
“…In [51], most recently, the authors use an MCA method as well as expert interactions to identify the relevance for the sustainability of different enablers of the industry 4.0 development. An approach to assess countries' industry 4.0 readiness level based on MCA methods and expert interactions is recently presented in [52]. The assessment via expert interactions is suitable for qualitative information; however, results may have higher uncertainty.…”
Section: Introductionmentioning
confidence: 99%